TAHAPAN KESALAHAN MENJAWAB SOAL MATEMATIKA MELALUI PROSEDUR NEWMAN SISWA KELAS IV SDN 1 WAMEO - Rimayasi Rimayasi; Nadir La Djamudi; Asrul Nazar (Sekolah Tinggi Pariwisata Mataram, 2023)
The purpose of this study was to describe the error phases that often occur in grade IV students when working on narrative questions on calculating the perimeter and area of ​​squares and rectangles at SDN 1 Wameo. This research is classified as field research using qualitative methods. Data collection was carried out using test and interview techniques. Methods of data analysis using include the stages of data reduction, data presentation, and drawing conclusions. The results of this study are that student errors at each stage of the Newman procedure, including the stages of reading questions, understanding questions, problem transformation, processing skills, and writing final answers, still occur quite frequently when working on questions about the perimeter and area of ​​squares and rectangles. These errors originate from students who do not fully understand the problem, which prevents them from finding out what is already known and what questions have been asked. In addition, for errors made during the transformation stage, especially because students cannot accurately transform story problems into mathematical models, students cannot create formulas to accurately calculate the perimeter, area, width, and length of squares and rectangles. As a result of errors at the level of process skills, students cannot solve problems using the right methods to perform mathematical operations. Due to the inability of students to do division and multiplication of two or more numbers correctly, errors in process skills appear. Finally, students make mistakes by using inappropriate processes. Mistakes made when writing final answers, such as when students fail to complete answers, fail to find final solutions, or make mistakes when writing final answers because they fail to double-check the answer sheet.